When the utility of micro-computed tomography collides with insect sample preparation: an entomologist user guide to solve post-processing issues and achieve optimal 3D models - Mensa, Francesco Simone; Muzzi, Maurizio; Spani, Federica; Tromba, Giuliana; Dullin, Christian; Di Giulio, Andrea (Applied Sciences, 2022)
Many techniques are used today to study insect morphology, including light and electron microscopy. Most of them require to specifically prepare the sample, precluding its use for further investigation. In contrast, micro-CT allows a sample to be studied in a non-destructive and rapid process, even without specific treatments that might hinder the use of rare and hard-to-find species in nature. We used synchrotron radiation (SR) micro-CT and conventional micro-CT to prepare 3D reconstructions of Diptera, Coleoptera, and Hymenoptera species that had been processed with 4 common preparation procedures: critical-point drying, sputter-coating, resin embedding, and air-drying. Our results showed that it is possible to further utilize insect samples prepared with the aforementioned preparation techniques for the creation of 3D models. Specimens dried at the critical point showed the best results, allowing us to faithfully reconstruct both their external surface and their internal structures, while sputter-coated insects were the most troublesome for the 3D reconstruction procedure. Air-dried specimens were suitable for external morphological analyses, while anatomical investigation of soft internal organs was not possible due to their shrinking and collapsing. The sample included in resin allowed us to reconstruct and appreciate the external cuticle and the internal parts. In this work, we demonstrate that insect samples destined to different analyses can be used for new micro-CT studies, further deepening the possibility of state-of-the-art morphological analyses.
Gesehen am 25.10.2022